src/HOL/Typedef.thy
author wenzelm
Sun, 02 Nov 2014 18:21:45 +0100
changeset 58889 5b7a9633cfa8
parent 58239 1c5bc387bd4c
child 60758 d8d85a8172b5
permissions -rw-r--r--
modernized header uniformly as section;

(*  Title:      HOL/Typedef.thy
    Author:     Markus Wenzel, TU Munich
*)

section {* HOL type definitions *}

theory Typedef
imports Set
keywords "typedef" :: thy_goal and "morphisms"
begin

locale type_definition =
  fixes Rep and Abs and A
  assumes Rep: "Rep x \<in> A"
    and Rep_inverse: "Abs (Rep x) = x"
    and Abs_inverse: "y \<in> A ==> Rep (Abs y) = y"
  -- {* This will be axiomatized for each typedef! *}
begin

lemma Rep_inject:
  "(Rep x = Rep y) = (x = y)"
proof
  assume "Rep x = Rep y"
  then have "Abs (Rep x) = Abs (Rep y)" by (simp only:)
  moreover have "Abs (Rep x) = x" by (rule Rep_inverse)
  moreover have "Abs (Rep y) = y" by (rule Rep_inverse)
  ultimately show "x = y" by simp
next
  assume "x = y"
  thus "Rep x = Rep y" by (simp only:)
qed

lemma Abs_inject:
  assumes x: "x \<in> A" and y: "y \<in> A"
  shows "(Abs x = Abs y) = (x = y)"
proof
  assume "Abs x = Abs y"
  then have "Rep (Abs x) = Rep (Abs y)" by (simp only:)
  moreover from x have "Rep (Abs x) = x" by (rule Abs_inverse)
  moreover from y have "Rep (Abs y) = y" by (rule Abs_inverse)
  ultimately show "x = y" by simp
next
  assume "x = y"
  thus "Abs x = Abs y" by (simp only:)
qed

lemma Rep_cases [cases set]:
  assumes y: "y \<in> A"
    and hyp: "!!x. y = Rep x ==> P"
  shows P
proof (rule hyp)
  from y have "Rep (Abs y) = y" by (rule Abs_inverse)
  thus "y = Rep (Abs y)" ..
qed

lemma Abs_cases [cases type]:
  assumes r: "!!y. x = Abs y ==> y \<in> A ==> P"
  shows P
proof (rule r)
  have "Abs (Rep x) = x" by (rule Rep_inverse)
  thus "x = Abs (Rep x)" ..
  show "Rep x \<in> A" by (rule Rep)
qed

lemma Rep_induct [induct set]:
  assumes y: "y \<in> A"
    and hyp: "!!x. P (Rep x)"
  shows "P y"
proof -
  have "P (Rep (Abs y))" by (rule hyp)
  moreover from y have "Rep (Abs y) = y" by (rule Abs_inverse)
  ultimately show "P y" by simp
qed

lemma Abs_induct [induct type]:
  assumes r: "!!y. y \<in> A ==> P (Abs y)"
  shows "P x"
proof -
  have "Rep x \<in> A" by (rule Rep)
  then have "P (Abs (Rep x))" by (rule r)
  moreover have "Abs (Rep x) = x" by (rule Rep_inverse)
  ultimately show "P x" by simp
qed

lemma Rep_range: "range Rep = A"
proof
  show "range Rep <= A" using Rep by (auto simp add: image_def)
  show "A <= range Rep"
  proof
    fix x assume "x : A"
    hence "x = Rep (Abs x)" by (rule Abs_inverse [symmetric])
    thus "x : range Rep" by (rule range_eqI)
  qed
qed

lemma Abs_image: "Abs ` A = UNIV"
proof
  show "Abs ` A <= UNIV" by (rule subset_UNIV)
next
  show "UNIV <= Abs ` A"
  proof
    fix x
    have "x = Abs (Rep x)" by (rule Rep_inverse [symmetric])
    moreover have "Rep x : A" by (rule Rep)
    ultimately show "x : Abs ` A" by (rule image_eqI)
  qed
qed

end

ML_file "Tools/typedef.ML"

end